Morphology and enzymatic activity of seedlings from wheat desiccated in pre-harvest - Fipke, Glauber Monçon; Deak, Evandro Ademir; Stecca, Jessica Deolinda Leivas; Bernardy, Daniele; Berger, Mirian; Tabaldi, Luciane Almeri; Martin, Thomas Newton (Acta Scientiarum. Agronomy, 2020)
Desiccation practiced during the preharvest period contributes to mechanized seed harvesting. This work aimed to verify whether wheat preharvest desiccation influences the morphological and physiological characteristics of the seedlings produced from the seeds of desiccated plants. The preharvest treatments included a combination of herbicides (glufosinate-ammonium, glyphosate, and paraquat) and phenological application stages (Zadoks: 83, 85, 87, and 92), as well as a control treatment (without application). Two wheat cultivars were used (BRS Parrudo and TBIO Sinuelo). Herbicide applications were observed to decrease the length and projected area of the shoots by 52 and 46%, respectively, as well as reduce the length, surface area and root volume when compared to the control treatment without application. The hydrogen peroxide concentration, as well as the enzymatic activity of guaiacol peroxidase, was observed to rise only in the treatments where the herbicides were applied. Physiologically, an increased hydrogen peroxide output was revealed, while the guaiacol peroxidase enzymatic activity increased in both cultivars, but with no effect noted in the superoxide dismutase enzymatic activity. The shoot and root morphology were negatively influenced, showing a rise in the enzymatic activity and hydrogen peroxide concentration in the seedlings from the desiccated plants.